Sensitivity and specificity of normalized truncated navicular height in assessment of static foot posture in children aged 6-12 years - Emad A. Aboelnasr; Hoda A. El-Talawy; Faten H. Abdelazim; Fatma A. Hegazy (World Scientific Publishing, 2019)
Background: Normalized truncated navicular height (NTNH) is a non-invasive, easy to perform, and simple clinical measure of static foot posture. However, its sensitivity and specificity in evaluation of the static foot posture in children have not been investigated yet. Objective: To investigate the intra-rater reliability, sensitivity, and specificity of NTNH in evaluation of the static foot posture in children using radiographic measure as a gold standard measure. Methods: A cross-sectional study of a random sample of 300 school children aged 6-12 years old. Intra-rater reliability, minimal detectable change, sensitivity, and specificity of NTNH were investigated. NTNH as a clinical measure of static foot posture was calculated and compared to the radiographic measure and displayed on the receiver operating characteristic (ROC) curve. Results: NTNH demonstrated an intra-rater reliability of ICC=0.98. The sensitivity and specificity of NTNH were 88.1% and 99.5%, respectively. The optimal cutoff point for the diagnosis of flat foot using NTNH in children aged 6-12 years is NTNH ≤0.19. Conclusion: NTNH is a sensitive and specific measure of static foot posture in the children aged 6-12 years. It is recommended to be used as a screening measure of static foot posture in children as it is easy, simple to perform, and a non-invasive clinical measure.